Technical Efficiency Analysis of Shallot Farming in Magetan Regency, Indonesia - Kartikawati, Herni; Kusnandar, Kusnandar; Widadie, Fanny (Universitas Negeri Gorontalo, 2025)
Technical efficiency is a crucial aspect of shallot production in Indonesia, yet comprehensive research analyzing the technical efficiency of shallot farmers in Magetan Regency remains limited. This study aims to measure the technical efficiency levels of shallot farming in Magetan Regency, identify the influencing factors, and provide relevant recommendations. This research contributes to the literature by providing the first comprehensive analysis of technical efficiency in Magetan Regency's unique highland-lowland agricultural context, offering evidence-based policy recommendations for sustainable shallot production intensification.The research method employed was a survey with a sample of 125 shallot farmers selected through a multistage random sampling technique. Data analysis utilized the Cobb-Douglas Stochastic Frontier production function with Maximum Likelihood Estimation (MLE), and technical efficiency was measured by comparing actual output to potential output. The results showed that the average technical efficiency of farmers reached 0.757, with 80% of farmers classified as efficient (≥ 0.7). Factors with a significant impact on production included the use of urea, labor, and seeds, which had a positive influence, while land area and organic fertilizer had a negative effect. These findings indicate inefficiencies in some production inputs, particularly in land management and the use of organic fertilizers. Optimizing fertilizer application, enhancing labor skills, and selecting quality seeds are strategic steps to improve technical efficiency. The findings have direct policy implications for agricultural extension programs, input subsidy allocation, and farmer training initiatives in Indonesia's shallot production centers.